Phytonanotechnology Synthesis and Characterization of Silver Nanoparticles using Methanolic Extract of L. Inermis: A Study of the Effect of Temperature, Ph on the Rate of Synthesis and Biochemical Properties - Hiba Adnan (Journal of Global Pharma Technology, 2018)
Phytonanotechnology synthesis methods are environmentally friendly, readily available, safe and nontoxic. In this study, methanolic extract of Lawsonia inermis has been used for the synthesis of silver nanoparticles. To improve the biological composition of natural nanoparticles, many parameters were investigated, and these were concentration of the extract, pH and temperature of the reaction. The characterization process was performed using techniques of UV-visible spectroscopy, Energy Dispersive X-Ray (EDX) and scanning Electron Microscopy (SEM).  The results illustrated that silver nanoparticles had a size of (150-600) nm and a spherical shape, showed SPR sharp peak between 390- 451 nm and EDX attested that Ag, W, Ru, Cl and C elements exhibited weight percentages of 69 %, 17%, 7.5%, 5.3% and 1.2 % respectively. The antibacterial activity was examined against two Gram positive bacteria (S. aureus and S. pneumoniae) and two Gram negative bacteria (E.coli and P. aeruginosa) by using the agar disk diffusion method , showed that silver nanoparticles had a strong effect against Gram positive bacteria and it is more than Gram negative bacteria. Antioxidant activity was also tested by DPPH test. The % inhibition values were found to be 82.66, 75.43, 71.57 and 62.67μg/ml for Ag NPs, ascorbic acid, L. inermis and BHA respectively at100 μg/ml.Key words: Silver nanoparticles, Law Sonia inermis, Antibacterial and Antioxidant activity.